Sobre la novel·la històrica actual - Simbor Roig, Vicent (Caplletra. Revista Internacional de Filologia, 1997)
One of the most important phenomena of the Catalan narrative, dating from 1975, is the impact of the historical novel which was abandoned in previous years. In this article there is a characterization of fact in general terms and a detailed study of remarkable authors (in particular, Josep Lozano and Joan Perucho).